2018
DOI: 10.1007/s00253-018-9187-y
|View full text |Cite
|
Sign up to set email alerts
|

A current view on long noncoding RNAs in yeast and filamentous fungi

Abstract: Long noncoding RNAs (lncRNAs) are crucial players in epigenetic regulation. They were initially discovered in human, yet they emerged as common factors involved in a number of central cellular processes in several eukaryotes. For example, in the past decade, research on lncRNAs in yeast has steadily increased. Several examples of lncRNAs were described in Saccharomyces cerevisiae and Schizosaccharomyces pombe. Also, screenings for lncRNAs in ascomycetes were performed and, just recently, the first full charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 88 publications
4
66
0
Order By: Relevance
“…We observed two major phenomena consistent with existing studies with respect to antisense transcription. First, as identified in other environmental conditions (Kim et al 2010;Till et al 2018;Wilhelm et al 2008), antisense transcription is induced pervasively in yeast undergoing cadmium stress. The distribution of genes with increased antisense transcripts monotonically skews towards more transcription through the 120-minute time course (Fig.…”
Section: Cadmium Treatment Induces Chromatin Dynamics As Distinct Temmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed two major phenomena consistent with existing studies with respect to antisense transcription. First, as identified in other environmental conditions (Kim et al 2010;Till et al 2018;Wilhelm et al 2008), antisense transcription is induced pervasively in yeast undergoing cadmium stress. The distribution of genes with increased antisense transcripts monotonically skews towards more transcription through the 120-minute time course (Fig.…”
Section: Cadmium Treatment Induces Chromatin Dynamics As Distinct Temmentioning
confidence: 89%
“…The second phenomena we observed pertains to genes whose sense transcription have changed. Previous studies have found that antisense transcription to be associated with both repression or activation of target genes (Kornienko et al 2013;Swamy et al 2014;Till et al 2018;Vance and Ponting 2014). Under cadmium stress, we identi-fied genes whose antisense transcripts increased with decreased sense transcription, such as with MET31 and UTR2, whose overexpression has been linked with endoplasmic reticulum stress (Miller et al 2010) (Supplemental Fig.…”
Section: Cadmium Treatment Induces Chromatin Dynamics As Distinct Temmentioning
confidence: 98%
“…34 In the past decade, studies of lncRNAs in fungi have steadily increased, such as in yeast, N. crassa, and T. reesei. 15,16,34 However, the characteristics of lncR-NAs in entomopathogenic fungi remain unclear. In this study, we evaluated lncRNAs in the entomopathogenic fungus C. militaris on a genome-wide level.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs that are involved in gene regulation have been identified in yeast and filamentous fungi (Till et al 2018a). Identification and manipulation of long noncoding RNAs represent another means to engineer filamentous fungi for improved heterologous protein production.…”
Section: Maximizing Transcription Of the Enzyme Gene Of Interestmentioning
confidence: 99%